2018
DOI: 10.1038/s41598-018-30476-9
|View full text |Cite|
|
Sign up to set email alerts
|

Revelation of early detection of co-seismic ionospheric perturbations in GPS-TEC from realistic modelling approach: Case study

Abstract: GPS-derived Total Electron Content (TEC) is an integrated quantity; hence it is difficult to relate the detection of ionospheric perturbations in TEC to a precise altitude. As TEC is weighted by the maximum ionospheric density, the corresponding altitude (hmF2) is, generally, assumed as the perturbation detection altitude. To investigate the validity of this assumption in detail, we conduct an accurate analysis of the GPS-TEC measured early ionospheric signatures related to the vertical surface displacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 29 publications
5
52
0
1
Order By: Relevance
“…Starting from 470 s, the TEC on the east‐northeast from the epicenter exceeds the background level, so that we can affirm reliable detection of a CID. We emphasize that this area of the first enhanced TEC corresponds to the uplift area as was estimated by Thomas et al () and as shown by white cross in Figure a. This first CID seems to further move southward while simultaneously extending westward.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Starting from 470 s, the TEC on the east‐northeast from the epicenter exceeds the background level, so that we can affirm reliable detection of a CID. We emphasize that this area of the first enhanced TEC corresponds to the uplift area as was estimated by Thomas et al () and as shown by white cross in Figure a. This first CID seems to further move southward while simultaneously extending westward.…”
Section: Resultssupporting
confidence: 77%
“…For the 2011 Sanriku‐oki earthquake, by using only data of satellite G07 Thomas et al () found extremely early first CID arrivals and explained them by a particular geometry of sounding at low‐elevation angles. Thomas et al () found that the first ionospheric detection took place at around 130 km of altitude, which is much below the ionization maximum of 275 km as follows from the International Reference Ionosphere (IRI) model (Bilitza et al, ; Figure a). Our results here confirm that for both G07 and G10 measurements the first CID occur 470–480 s after the earthquake (Figures b–d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of these two TEC enhancements corresponded to the location of two segments of coseismic crustal slip as it was shown by seismologists (e.g., Simons, ; Bletery et al, ; Figure a). More recently, Thomas et al () and Astafyeva and Shults () demonstrated that the GNSS seismo‐ionospheric imagery can work for moderate earthquakes as well. Astafyeva and Shults () also noted that lower resolution data sampling, such as 15 or 30 s, which so far is a standard resolution for GNSS data, will, most likely, not work efficiently.…”
Section: Ionospheric Response To Earthquakes and Tsunamismentioning
confidence: 99%
“…Within the past two decades, numerous simulation techniques have been developed. For instance, ray tracing is the simplest, although not the most precise, way to reproduce near‐field ionospheric signatures of earthquakes and volcanic eruptions (Calais et al, ; Dautermann, Calais, & Mattioli, ; Heki et al, ; Heki & Ping, ; Rolland et al, ; Thomas et al, ). To model CSID propagation in the far‐field and the ionospheric signatures of Rayleigh surface waves and tsunamis, normal mode summation technique shows promising results (Artru et al, ; Artru et al, ; Coïsson et al, ; Lognonné et al, ; Rakoto et al, ; Rolland, Lognonné, & Munekane, ).…”
Section: Future Perspectivesmentioning
confidence: 99%